National responsibility towards the migrant workers - Siddiqui, Tasneem; Refugee and Migratory Movements Research Unit. (Dhaka : Refugee and Migratory Movements Research Unit, 1998)
Papers presented at a workshop held during 1997.
Includes bibliographical references (p. 22-23).
Keywords: Migrant labor -- Bangladesh -- Congresses